2013
DOI: 10.1371/journal.pone.0080425
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Impacts of the Inhibition of the Molecular Chaperone Hsp90 on the T-Cell Proteome Have Implications for Anti-Cancer Therapy

Abstract: The molecular chaperone Hsp90-dependent proteome represents a complex protein network of critical biological and medical relevance. Known to associate with proteins with a broad variety of functions termed clients, Hsp90 maintains key essential and oncogenic signalling pathways. Consequently, Hsp90 inhibitors are being tested as anti-cancer drugs. Using an integrated systematic approach to analyse the effects of Hsp90 inhibition in T-cells, we quantified differential changes in the Hsp90-dependent proteome, Hs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 71 publications
3
40
1
Order By: Relevance
“…This approach, which was originally developed to provide accurate and data-driven normalization factors to quantitative real-time PCR data, 42 was then applied to RNA sequencing count data to identify the most variable genomic features 43 and successfully usedto normalize the nCounter miRNA assay count data as well. 44,45 Differences in exosome concentration between healthy donors and CLL patients, as well as IGHV-mutated and -unmutated CLL patients, were examined using 2-sample t tests with unequal variances. Paired t tests or mixed effects models were used to assess differences in exosome concentration/production between conditions within patient samples (eg,, ibrutinib in the presence of a-IgM stimulation vs stimulation alone).…”
Section: Discussionmentioning
confidence: 99%
“…This approach, which was originally developed to provide accurate and data-driven normalization factors to quantitative real-time PCR data, 42 was then applied to RNA sequencing count data to identify the most variable genomic features 43 and successfully usedto normalize the nCounter miRNA assay count data as well. 44,45 Differences in exosome concentration between healthy donors and CLL patients, as well as IGHV-mutated and -unmutated CLL patients, were examined using 2-sample t tests with unequal variances. Paired t tests or mixed effects models were used to assess differences in exosome concentration/production between conditions within patient samples (eg,, ibrutinib in the presence of a-IgM stimulation vs stimulation alone).…”
Section: Discussionmentioning
confidence: 99%
“…There is also the concern that H90Ins could impact the effectiveness of tumor suppressor pathways (Fierro-Monti et al 2013); (Manjarrez et al 2014). HSP90 interacts with a large portion of the proteome and is involved in maintaining tumor promoting as well as tumor suppressing cellular components (Taipale et al 2014); (Nony et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…34,35 The majority of Hsp90's activity occurs in the cytosol, where it forms protein-protein interactions with approximately 60% of all cellular kinases and 30% of all ubiquitin ligases. 34,36 In addition, Hsp90 contributes to the maturation of hormone receptors and kinases that are essential for oncogenesis in hormone-dependent cancers.…”
Section: Macrocycles As Anticancer Agentsmentioning
confidence: 99%
“…Recent proteomic studies have shown that geldanamycin alters cellular protein levels through a decrease in de novo protein synthesis and a reduction in protein stability. 35,64 The complex and interlinking protein networks that are affected by geldanamycin form one arm of the apoptotic process, but the induction of metabolic stress through the reduction of the compound also contributes to cell death. Two enzymes metabolise the benzoquinone moiety of geldanamycin and enhance the macrocycle's potency or contribute to its toxicity.…”
Section: Geldanamycinmentioning
confidence: 99%